2012
DOI: 10.1016/j.cryobiol.2012.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the exposure to methyl-β-cyclodextrin prior to chilling or vitrification on the viability of bovine immature oocytes

Abstract: The present study aimed to evaluate the effect of methyl-β-cyclodextrin (MβCD) as a cholesterol loader to change oocyte plasma membrane and increase its tolerance toward cryopreservation. The first and second experiments were conducted to investigate if MβCD could improve nuclear and cytoplasmic maturation after oocyte exposure to cold stress for 10 or 30 min, respectively. No differences (P>0.05) in either experiment in the metaphase II (MII) rate of oocytes exposed to MβCD and cold stress; but these oocytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 42 publications
2
17
0
Order By: Relevance
“…In the first study [14], the authors showed that cholesterol diffused through cumulus cells and reached the oocyte but failed to reflect these effects in the production of embryos. The same methodology was applied later in immature bovine oocytes [15]. In this case, both the presence of serum and the compact structure of the cumulus of immature oocytes could have limited the availability of MβCD/cholesterol complexes, affecting the results collected.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the first study [14], the authors showed that cholesterol diffused through cumulus cells and reached the oocyte but failed to reflect these effects in the production of embryos. The same methodology was applied later in immature bovine oocytes [15]. In this case, both the presence of serum and the compact structure of the cumulus of immature oocytes could have limited the availability of MβCD/cholesterol complexes, affecting the results collected.…”
Section: Discussionmentioning
confidence: 99%
“…Modulation of plasma membrane cholesterol to increase post-cryopreservation survival is currently a booming topic for the male gamete of different species (for review, see [13]) but has been little addressed in oocytes. Previously, Horvath and Seidel [14] and, more recently, Spricigo et al [15] reported the use of this method to add cholesterol to bovine oocytes prior to vitrification. Horvarth and Seidel [14] claimed that cholesterol could enter mature oocytes through the cumulus cells and the zona pellucida , improving its viability after vitrification in a chemically defined system.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations